INDOOR THERMAL COMFORT ASSESSMENT OF NATURALLY VENTILATED ATRIUMS IN SINGAPORE - Hien, Wong Nyuk; Gabriela, Osrithalita; Tan, Erna; Jusuf, Steve Kardinal (DIMENSI (Journal of Architecture and Built Environment), 2017)
This research looks into the aspect of Thermal Comfort (TC) in naturally ventilated (NV) buildings, in this case NV atriums. Compared to fully air-conditioned buildings, NV buildings tend to have better indoor air quality (IAQ), but worse TC. Therefore, this research investigates the range of acceptable temperature and wind speed in order to achieve thermal comfort for naturally ventilated atriums. Data was collected through field survey in three different buildings of NV atriums and were used to develop and validate the TC model. The data collected from field survey represent visitors’ TC perception in atrium environment, and in-situ environmental measurement also records the characteristics of NV atrium in each area, such as solar radiation, air temperature, relative humidity, and intermittent wind. At the same time with the indoor field survey, a weather station was installed on the roof of the building to measure the micro-meteorological condition. Thermal comfort prediction model was developed from the statistical analysis of the field survey data. The acceptable range to achieve thermal comfort for NV atrium was analyzed. The air temperature of 31°C was determined as the boundary condition. Based on the result of Predicted Mean Vote (PMV) formula, PMV 1 is the highest acceptable value with wind speed required is 0.51 m/s and PMV 0.8 is recommended to achieve the best thermal comfort with wind speed required is 0.78 m/s.